2013
DOI: 10.1016/j.eats.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Repair of Full-Thickness Gluteus Medius Tears

Abstract: Tears in the gluteus medius and minimus tendons recently have emerged as an important cause of chronic greater trochanteric pain syndrome. Increasing recognition of the gluteal insertion as a cause of chronic pain and weakness, as well as technologic advances in endoscopic hip surgery, has made gluteal insertional repair a rapidly emerging technique in minimally invasive surgery of the hip. We present an endoscopic double-row technique for gluteal insertional repair that allows for visualization, debridement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…Second, excessive resection of the ITB may result in herniation of the underlying soft tissue and painful external snapping [81]. Third, it could also have a deleterious effect on abductor muscle function as a result of reduced potential for the gluteus maximus and TFL to control the hip via their attachments to the ITB [86]. Fourth, because of compromise of one of the pelvic postural control structures, the patient may resort to trunk lateral flexion to control the motion of the pelvis relative to the hip.…”
Section: Surgical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, excessive resection of the ITB may result in herniation of the underlying soft tissue and painful external snapping [81]. Third, it could also have a deleterious effect on abductor muscle function as a result of reduced potential for the gluteus maximus and TFL to control the hip via their attachments to the ITB [86]. Fourth, because of compromise of one of the pelvic postural control structures, the patient may resort to trunk lateral flexion to control the motion of the pelvis relative to the hip.…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…The longest period of follow-up after open tendon repair has been 5 years, after which 16 of 19 patients maintained significant improvements gained in the first 12 months, as measured by the Harris Hip Score and Lower Extremity Activity Scale. Gluteal tendon repairs can now be performed endoscopically [81,83,86], which is less invasive and is associated with reduced post-operative infection, scarring and pain, and more accelerated rehabilitation [86]. Endoscopic techniques, however, require greater surgical skill and are generally unsuitable for larger tears or tendon detachments where there is retraction of the muscle and greater visualization is required [83].…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…[12][13][14] However, with advancements in endoscopic instruments and techniques, there has been a recent increase in the prevalence of endoscopic repairs. [15][16][17][18] The aim of this systematic review was to compare the outcomes of open versus endoscopic gluteal repairs and provide an algorithm regarding the indications and benefits for each approach.…”
mentioning
confidence: 99%
“…1,3,4,7 Meta-analyses of the existing case series have shown that endoscopic repair leads to similar improvement in pain and function, albeit with fewer complications compared with open techniques. 3,4 Thus, endoscopic repair has become the favored method.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Gluteal tears are analogous to tears of the rotator cuffdpathophysiologically and clinically. Both injuries most often result from a chronic, degenerative process, with or without a proceeding traumatic event, 1 and are classified as either full-or partialthickness tears (full-thickness gluteus tears often lead to significant weakness in hip abduction). 1 The first step in management of gluteal medius tears is nonoperative, including physical therapy, activity modification, and nonsteroidal anti-inflammatory drugs.…”
mentioning
confidence: 99%